PHOTODEGRADATION OF 3-(3,4- DICHLOROPHENYL)-1,1-DIMETHYLUREA IN PRESENCE OF NATURAL IRON OXIDE UNDER UV IRRADIATION (Sciences & Technology. A, exactes sciences, 2014)
Heterogeneous photodegradation of Linuron under UV irradiation was investigated. Natural iron oxide (NIO) was used in this study, to take a closer look at its adsorption capacity in the dark. The results obtained showed that the substrate photolysis is very slowly in artificial light (λ = 365nm). However, the introduction of oxalic acid (Ox) in the system improves the degradation process greatly. The dependence of Linuron degradation was attributed to the formation of the dissolved Fe-Ox in the solution and the adsorbed Fe-Ox on the surface of natural iron oxide. The effect of different parameters such as the oxalate concentration, pH and initial concentration of NIO on the photodegradation were studied in the iron oxide/ oxalate system. The results demonstrated that the optimal pH should be in the range of 2–3. The system efficiency is directly proportional to the concentration of polycarboxylate ions. The optimum mass of NIO used a good inducing disappearance of linuron was 1g.L-1. Furthermore, changes in the concentrations of Fe3+ and Fe2+ ions in the photo-reaction were also strongly dependent on the initial oxalate and iron oxide concentration. The use of 2% of isopropanol as a scavenger confirmed the intervention of hydroxyl radicals in the photodegradation of linuron.